CLARIFICATIONS ON THE PRINCIPLE OF THE AUTONOMY IN LOCAL PUBLIC ADMINISTRATION MANAGEMENT - BILOUSEAC, Irina; ZAHARIA, Petronela (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
The problem of autonomy exists in any democratic state, being a fundamental principle which underpins the development of local government. Local collectivities activity is inextricably linked to the concept stated, local autonomy is the right of communities to solve and manage themselves public issues. Our scientific approach aims at defining, analyzing and configuring the structural elements of local autonomy. To understand the complex meaning of autonomy in local public administration management we intend to identify the elements that form its structure and gives it consistency, i.e. organizational, functional and administrative components. In addition, the provision and implementation of local autonomy is a goal of all European states, their constitutions assigning a primordial role to this principle, whose importance in the organization and functioning of local public administration is undeniable.